Densidade de plantio e substâncias húmicas no cultivo do tomateiro - (:unkn) unknown (Universidade Estadual de Goiás, 2015)
The objective of this study wasto evaluate different doses of humic and fulvic acids in the development and yield of table tomato cultivated with different planting densities. The project was developed in the experimental field of the State University of Goias (UEG), Ipameri-GO. The experimental design adopted wasrandomized complete block, arranged in factorial 5 x 2 (doses of humic and fulvic acids x arrangement plants) with four replications and 10 plants in the useful area of each plot. To evaluate the effect of plant density was adopted spacings of 0,3 and 0.5 m between plants and 1.0 m between rows, corresponding respectively to the population of 33,333 and 20,000 plants ha-1 with different dosages (0 20, 40, 60 and 80 L ha-1 ) humic and fulvic acids. Was used the hybrid tomato Santy. The evaluation of the development and yield of tomato was performed after transplanting in the field. Data were subjected to analysis of variance (F test) and the averages compared by Tukey test at 5% probability. The yield of tomato was significantly modified by different spacings. The pH, titratable acidity, fruit degree of firmness and soluble solids content of the fruit were not altered by varying spacings. Doses of humic acids and fulvic influenced chlorophyll content, fruit firmness and the average number of fruits.
Keywords: Solanum lycopersicum L.; ácidos húmico e fúlvico; espaçamentos; produtividade; Solanum lycopersicum L.; humic acids and fulvic; spacing; yield; CIENCIAS AGRARIAS